Oxygen Saturation Targets in Preterm Infants and Outcomes at 18–24 Months: A Systematic Review - Manja, Veena (Pediatrics, 2017)
CONTEXT: The optimal oxygen saturation target for extremely preterm infants remains unclear. OBJECTIVE: To systematically review evidence evaluating the effect of lower (85%–89%) versus higher (91%–95%) pulse oxygen saturation (Spo(2)) target on mortality and neurodevelopmental impairment (NDI) at 18 to 24 months. DATA SOURCES: Electronic databases and all published randomized trials evaluating lower versus higher Spo(2) target in preterm infants. STUDY SELECTION: A total of 2896 relevant citations were identified; 5 trials were included in the final analysis. DATA EXTRACTION: Data from 5 trials were analyzed for quality of evidence and risk of bias. LIMITATIONS: Limitations include heterogeneity in age at enrollment and comorbidities between trials and change in oximeter algorithm midway through 3 trials. RESULTS: There was no difference in the incidence of primary outcome (death/NDI at 18–24 months) in the 2 groups; risk ratio,1.05, 95% confidence interval 0.98–1.12, P = .18. Mortality before 18 to 24 months was higher in the lower-target group (risk ratio,1.16, 95% confidence interval 1.03–1.31, P = .02). Rates of NDI and severe visual loss did not differ between the 2 groups. Proportion of time infants spent outside the target range while on supplemental oxygen ranged from 8.2% to 27.4% <85% and 8.1% to 22.4% >95% with significant overlap between the 2 groups. CONCLUSIONS: There was no difference in primary outcome between the 2 Spo(2) target groups. The collective data suggest that risks associated with restricting the upper Spo(2) target limit to 89% outweigh the benefits. The quality of evidence was moderate. We speculate that a wider target range (lower alarm limit, 89% and upper, 96%) may increase time spent within range, but the safety profile of this approach remains to be determined.